Campus Prophets, Spiritual Guides, or Interfaith Traffic Directors? The Many Lives of College and University Chaplains. Issue 2 (1st May 2021) - Schmalzbauer, John
Abstract: What is the role of the chaplain on the 21st century campus? Comparing today's chaplains to their mid-century counterparts, this article presents findings from the National Study of Campus Ministries. Based on a 2006 survey of 1, 659 campus religious professionals, it focuses on a subsample of 335 chaplains employed in private colleges and universities and 80 in-depth interviews with college chaplains conducted prior to the survey. While chaplains perform many different roles, this study focuses on three that capture the changing place of the profession in the 21st century: campus prophets, spiritual guides, and interfaith traffic directors.